Instrumen Investasi Syariah di Pasar Modal: Komparasi Perkembangan Indonesia dan Dinamika Global - Frida Eka Ristanti; Helmalia Oktaviana; Muhammad Aqim Adlan; Dede Nurrohman (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study provides a comparative analysis of the development of Islamic investment instruments in Indonesia and global markets during the 2010–2025 period. It aims to map the evolution of instruments, compare product structures, regulatory frameworks, and supervisory systems, and identify supporting factors and constraints affecting market competitiveness. The research employs a qualitative-descriptive method through literature review and comparative analysis of regulatory documents, market reports, fatwas, books, and scholarly journals. The findings indicate that Indonesia’s Islamic capital market has experienced significant growth through the strengthening of Islamic stocks, sovereign sukuk, green sukuk, and the initial development of digitalized instruments. However, compared with global markets such as Malaysia, the United Kingdom, and GCC countries, Indonesia still faces limitations in product diversification, secondary market liquidity, and regulatory harmonization. Regulatory, institutional, technological, and sustainability factors are key determinants shaping the dynamics of Islamic investment instrument development. The study concludes that Indonesia has strategic potential to accelerate the growth of its Islamic capital market, but stronger policy integration, product innovation, and digital transformation are needed to improve global competitiveness.